Therapeutic Strategy for Acute Spinal Cord Contusion Injury: Cell Elimination Combined with Microsurgical Intervention - Kalderon, Nurit (Public Library of Science, 2007)
BACKGROUND: No cure is available for human spinal cord injury. Cell elimination by localized radiation therapy that is timed within 2–3 weeks postinjury can facilitate repair of structure and function in transected rat spinal cord. In pilot studies in contusion spinal cord injury, a model similar to crush/fracture injury in human, we did not observe the expected beneficial effects of radiation therapy. Long forgotten data show that in contusion/crush injury, fluid accumulation from hemorrhage is critical. Alfred Reginald Allen observed that the most devastating sequelae in contusive injury are secondary to fluid accumulation which could be alleviated by surgical intervention, midline slits (myelotomy) at the lesion site. METHODS AND FINDINGS: Here, we tested whether release of fluid buildup by microsurgery (partial myelotomy) would affect the structural outcome of radiation therapy in the severely contused rat spinal cord. Surgical intervention alone significantly enhanced tissue and functional preservation in the contused cord, thus confirming Allen's observations. Combining partial myelotomy with radiation therapy that is specifically timed postinjury elicited substantial beneficial therapeutic outcome; it led to significant increase in tissue repair/preservation compared with the group that received surgical intervention only, as determined by histology and in vivo MRI. Altogether, the combined treatments led to a 1.8 fold increase in tissue repair/preservation as compared with the contused group. CONCLUSIONS: The data suggest that a clinical protocol could be developed to treat acute human spinal cord injury through conventional clinical procedures, a combination of microsurgical manipulation and radiation therapy. These also suggest it is imperative to first prevent the secondary damage caused by fluid accumulation for a cure to be possible.